Posner-Schlossman syndrome relapse following inactivated COVID-19 vaccination in China - Sheng, Qilian; Sun, Yanan; Zhai, Ruyi; Fan, Xintong; Ying, Yue; Kong, Xiangmei (Frontiers in Public Health, 2023)
Introduction This retrospective study aims to present the characteristics of Posner-Schlossman syndrome (PSS) relapse following inactivated COVID-19 vaccination. Methods From 2020 to 2022, 12 out of 106 PSS patients undergoing relapses after any dose of inactivated COVID-19 vaccines were enrolled. Medical histories, information on the vaccination and systemic adverse events were collected. Patients were treated with corticosteroids, intraocular pressure (IOP)-lowering drugs and systemic immunosuppressive agents (if needed). Daily regimen and release course were noted. Results The recurrence rate after vaccination was 11.32% (12/106, 95% CI: 5.29%–17.35%) among 106 PSS patients we surveyed. All the 12 patients were inoculated with inactivated COVID-19 vaccines developed by Sinopharm, China. The mean time of relapse was 5.27 ± 3.72 days (range: 1–13 days, median: 4 days). Higher IOP and more keratic precipitates (KPs) were seen in the relapse following vaccination (33.55 ± 12.99 mmHg, 91.67% had KPs compared to 25.38 ± 3.80 mmHg, 33.33% had KPs in previous relapse, P = 0.009). The mean release course was 30.71 ± 34.74 days for the relapse following vaccination and 7.33 ± 6.51 days for previous relapses. The attack frequency before and after vaccination was 3.56 ± 2.07 and 9.11 ± 7.34 times per year (P = 0.044). Higher daily doses of corticosteroids, IOP-lowering drugs and ganciclovir were needed to maintain stable course, though the difference did not reach statistical significance. Discussion More frequent relapses and harder control of IOP were found in PSS relapse following COVID-19 vaccination. Ophthalmologists need to be aware of the group vulnerability and take precautions, though the pathogenesis is still under investigation.